Agbeyewo Ewi Ayaba Laarin Awon Oyo-Osun (An Appraisal of the Poetry of Obas' Wives among Oyo-Osun People) - Oyeweso, Musibau Oyewale (2015)
This study examined poetry of Oba’s wives among the Oyo-Osun people. It analysed the nature, language and performance of the poetry of Oba's wives in the society, with a view to highlighting its significances.